PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK UNTUK MENGOPTIMALKAN KETERAMPILAN MEMBACA PERMULAAN DIKELAS II SDN 2 MEURANDEH - Angraini, Sinta; Mulyahati, Bunga; Kumala Sari, Cut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the issue of low early reading skills. Consequently, the study aimed to develop "Big Book" learning media and to determine its validity, practicality, and effectiveness in optimizing the early reading skills of second-grade students at SDN 2 Meurandeh. This study employed the Research and Development (R&D) method, specifically utilizing the ADDIE model (analysis, design, development, implementation, and evaluation). The research was conducted at SDN 2 Meurandeh, involving expert validators, a Grade IIA teacher, and 23 second-grade students. Data were collected through observations, interviews, validation questionnaires, and response questionnaires from both the teacher and students. The results indicated that the Big Book learning media achieved validation scores of 90% for the material aspect (highly valid), 96% for the language aspect (highly valid), and 90% for the media aspect (highly valid). Regarding practicality, the media received a teacher response score of 98% (highly practical) and a student response score of 98% (highly practical). The average pretest score of 61% increased to 93% in the posttest. Furthermore, the average N-gain score was 0.8591, falling into the high category. These results demonstrate that the Big Book learning media is feasible, practical, and effective for optimizing early reading skills among second-grade students at SDN 2 Meurandeh.